Healthcare seeking behavior for acute illnesses among adult Aborigine communities (Orang Asli) in Cameron Highlands, Malaysia: a house-to-house survey - Danaletchumy Ganesan; Sumaira Hussain; Chandrashekhar T. Sreeramareddy (PAGEPress Publications, 2024)
Indigenous people often have poor health due to a lack of access to health care. We studied healthcare-seeking behaviors and associated factors of Orang Asli populations living in remote hilly areas of Peninsular Malaysia. A house-to-house survey was done in 11 of 28 randomly selected villages. A sample of 225 Adults aged 18 years and above were interviewed about healthcare-seeking behavior for an episode of illness 30 days before the survey date. Factors associated with appropriate healthcare-seeking behavior as determined by binary logistic regression analyses. More than a third of the Orang Asli adults (88/225) did not consult any healthcare provider (39%) for which 'illness does not need treatment' or 'not sick enough' (22%) and no transportation (12%) were the main reasons. Being of older age (aOR 0.95, 95%CI 0.9, 0.98), income higher than 500 Malaysian Ringgits per month (aOR 2.35, 95%CI 1.04, 5.39), perception of illness as 'severe'(aOR 54.79 95% CI 12.61, 239.9), and closer distance of health facility (aOR 0.86 95% CI 0.81, 0.93) were associated with appropriate healthcare-seeking behavior. Health promotion campaigns are needed to improve awareness about common illnesses and improve care-seeking behavior.